Exploring the influence of reality television on financial behavior - Rasure, Erika M. (Kansas State University, 2015)
Viewership of reality television has been indicated to influence behaviors among individuals and groups, as existing literature has linked reality television viewership to an increase in the likelihood of demonstrating other non-financial behaviors. The literature notes increases in risky sexual and dating behavior, increases in tobacco, drug, and alcohol use, and increases in violent behavior. This dissertation examined the perceptions of the influence of reality television on financial behavior. Situational reality television programming was found to have the greatest influence on the financial behaviors of college students. Ten college students were interviewed using a phenomenological qualitative approach. There were four primary findings from this study. The first was that reality television has the ability to inform the financial behavior of college students. Second, an individual’s connection to his or her social system has an influence on financial behavior. Third, reality television does have the ability to influence financial behavior change and fourth, reality television influences the meaning of money as perceived by the respondents. The results of this study provide valuable information to promote further inquiry as to how reality television and other forms of media influence financial behavior.
Keywords: Reality television; Financial behavior; Financial socialization; College students; Social cognitive theory of mass communication; Spending; Cognitive Psychology (0633); Education Finance (0277); Mass Communications (0708)